The Main Character of The Short Story Taher wa Nadia by Amin Salamah: Psychological Analysis with Daniel Goleman Theory - Hanum, Lailatul Fitria; Ahmad Kholil (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2025)
The short story